PEMETAAN DAERAH BENCANA PADA DESTINASI KOTA PALOPO (STUDI KASUS BENCANA BANJIR DAN LONGSOR) - Ridwan, Masri; Darwis; Zainuddin , Agus; Muh Kasim; Muh Yahya (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
As a Tourism Development in South Sulawesi, Palopo city has been stipulated as a Regional Tourism Strategic Area, has potential resources and a widely recognized image. Palopo City is an area disaster-prone, including landslides and floods. Therefore, a disaster hazard management approach is needed to support the government’s campaign to implement sustainable tourism that safety from disasters. This study has two aims. Number one is to map the distribution of tourist sites in Palopo City. Number two is to analyze the threat of disaster in tourist sites. The methods used in this study were Focus Group Discussion (FGD) using the primary and secondary data through Geographic Information System (GIS) analysis to produce the distribution of tourist objects in disaster-prone areas. The results of this study indicated that the western part of Palopo city has a threat of soil erosion in 9 tourist sites, while the eastern has a flood threat in 12 tourist sites. The research recommendation to revise the Regional Spatial Planning (RTP) of Palopo City in 2012 – 2032, oriented toward sustainability. Tourist objects that are related to the areas are: protected forests, disaster-prone, and conflicts are accommodated in Regional Spatial Planning (RTP); the operational details of the Regency/City have not been described in detail in Regional Spatial Planning (RSP) for example in flood and landslide disaster areas in the Tourism object at Lokkoe Langkanae, BRC Carnival Park, Naggala III natural tourism park, Bambalu natural baths, Kalo Dewata Battang Cave, Lummarrang river and Siguntu waterfall.